Balance of competencies between the federal government and regional governments In Iraq / comparative study - Abdullqadir, Binak Abdullah (Journal of Legal and Political Studies, 2025)
Federal systems differ in the distribution of powers between the federal government and regional governments. This balance requires the availability of guarantees that contribute to preserving the federal balance, which are: the constitutional guarantee, which is represented by the existence of a federal constitution that stipulates the distribution of powers between the center and the region and is characterized by rigidity and supremacy. The second guarantee is represented by the involvement of the states or regions in expressing the general will of the federal state. Finally, any A federal system with a supreme judicial authority that decides on the problems of the union and disputes related to its relations Keywords: balance of powers, federal government, regional government. Federal State, Federal Constitution
Keywords: balance of powers; federal government; regional government Federal State; Federal Constitution